1984
DOI: 10.1182/blood.v63.1.73.73
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of oxygenated red blood cells in sickle cell (HbSS) disease

Abstract: Little data exist for the mechanical properties of individual irreversible or reversible sickle cells (ISC and RSC, respectively), nor is the process of ISC formation well understood. For oxygenated ISC and density-fractionated RSC, we have used micropipette techniques to measure cell surface area (SA) and volume (V), membrane shear elastic modulus (mu), time constant for viscoelastic shape recovery (tc), and hence to calculate membrane surface viscosity (eta = mu X tc). Volume loss associated with increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 0 publications
2
46
0
Order By: Relevance
“…Decreased cellular deformability of oxygenated sickle cell anemia RBC has been documented using a variety of techniques, including viscometry, filtration, ektacytometry, and micropipet aspiration of individual cells (17,32,35,49,61,102,127,141). In these measurements, reduction in RBC deformability is manifested, respectively, by increased viscosity of blood (32), decreased filtration rate of dilute cell suspension through narrow pores (127,141), decreased ability of cells to undergo deformation in shear fields (17,35), and increased aspiration pressures needed to induce entry of cells into micropipets (49,61,102).…”
Section: Deformability Of Oxygenated Sickle Rbcmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased cellular deformability of oxygenated sickle cell anemia RBC has been documented using a variety of techniques, including viscometry, filtration, ektacytometry, and micropipet aspiration of individual cells (17,32,35,49,61,102,127,141). In these measurements, reduction in RBC deformability is manifested, respectively, by increased viscosity of blood (32), decreased filtration rate of dilute cell suspension through narrow pores (127,141), decreased ability of cells to undergo deformation in shear fields (17,35), and increased aspiration pressures needed to induce entry of cells into micropipets (49,61,102).…”
Section: Deformability Of Oxygenated Sickle Rbcmentioning
confidence: 99%
“…Decreased cellular deformability of oxygenated sickle cell anemia RBC has been documented using a variety of techniques, including viscometry, filtration, ektacytometry, and micropipet aspiration of individual cells (17,32,35,49,61,102,127,141). In these measurements, reduction in RBC deformability is manifested, respectively, by increased viscosity of blood (32), decreased filtration rate of dilute cell suspension through narrow pores (127,141), decreased ability of cells to undergo deformation in shear fields (17,35), and increased aspiration pressures needed to induce entry of cells into micropipets (49,61,102). These studies documented the abnormal rheologic properties of oxygenated sickle cell anemia RBC and, in addition, showed that there is marked heterogene-ity in the extent of rheologic abnormalities of RBC in individual blood samples and among blood samples from different individuals (3,7,49,79,102,132).…”
Section: Deformability Of Oxygenated Sickle Rbcmentioning
confidence: 99%
“…With increasing density, there was a progressive increase in MCHC and ISC%, a right shift in the OSC, and impaired deformability of oxygenated erythrocytes. This rheological impairment of dense SS cells with a relatively high MCHC has also been demonstrated by viscometric (Kaul et al, 1983), micropipette aspiration (Evans et al, 1984;Nash et al, 1984) and ektacytometric techniques (Clark et al, 1980;Sorette et al, 1987). The increase in viscosity on deoxygenation of solutions of sickle haemoglobin is also dependent on haemoglobin concentration (Chien et al, 1982).…”
Section: Discussionmentioning
confidence: 64%
“…The methods most commonly used to study erythrocyte suspensions are viscometry (Dintenfass, 1964;Charache and Conley, 1964;Chien et al, 1970Chien et al, , 1982Drasler et al, 1989), filtration (Weed et al, 1969;Messer and Harris, 1970;Chien et al, 1971;Lessin et al, 1977;Reinhart et al, 1984;Arai et al, 1990), and ektacytometry Mohandas, 1975, 1977;Groner et al, 1980;Sorette et al, 1987). The micropipette technique is useful to study single cell deformability, including cell membrane properties (Evans and Hochmuth, 1976;LaCelle et al, 1977;Nash et al, 1984). In addition to cell suspension studies, viscometry is also useful for determining the rheological properties of Hb S solutions (Briehl, 1981;Chien et al, 1982;Danish et al, 1987;Drasler et al, 1989).…”
Section: Experimental and Theoretical Backgroundmentioning
confidence: 99%
“…The deformability properties of erythrocytes are critical determinants of flow in the microcirculation (Skalak, 1969;Evans and Hochmuth, 1976;Chien et al, 1982Chien et al, , 1987Linderkamp and Meiselman, 1982;Nash and Meiselman, 1982;Nash et al, 1984Nash et al, , 1986Pfafferott et al, 1985;Shohet and Mohandas, 1988). Abnormalities of these properties are thought to be the principal cause of the pathophysiology of sickle cell disease and other hemoglobinopathies (Schechter et al, 1987).…”
Section: Introductionmentioning
confidence: 99%